2014
DOI: 10.1007/s11418-014-0857-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and chemical characterization of white and red peony root derived from Paeonia lactiflora

Abstract: Two kinds of peony roots—white peony root (WPR) and red peony root (RPR)—are used for different remedies in traditional Chinese medicine; however, most of them are derived from the same botanical origin, Paeonia lactiflora. The difference between WPR and RPR has been debated for a long time. This study attempted to clarify the genetic and chemical characteristics of WPR and RPR in order to provide a scientific dataset for their identification and effective use. The nucleotide sequence of nrDNA internal transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
(22 reference statements)
1
30
0
Order By: Relevance
“…37,38 In human colon cancer LoVo cells, paeonol blocked cell cycle at the G1 to S transition and induced apoptosis. 39 In HT-29 cells, paeonol inhibited proliferation 40 and showed a synergetic antiproliferative effect when combined with 5-FU.…”
Section: Actions Of Paeonia (Chi Shao)mentioning
confidence: 99%
“…37,38 In human colon cancer LoVo cells, paeonol blocked cell cycle at the G1 to S transition and induced apoptosis. 39 In HT-29 cells, paeonol inhibited proliferation 40 and showed a synergetic antiproliferative effect when combined with 5-FU.…”
Section: Actions Of Paeonia (Chi Shao)mentioning
confidence: 99%
“…4,8,23,24) In this study, we found that several cultivar samples (samples 3, 6, 9, 13, 15) had the similar metallomic profiles to those of crude drugs that were relatively homogenous. We demonstrated the possibility of usefulness of those cultivars for medicinal use and our metallomic analysis as a simple method for verifying the quality of Paeoniae Radix.…”
Section: Discussionmentioning
confidence: 56%
“…The herbal samples used in this study were all authenticated, genetically analyzed and certified to have the same characteristic nucleotide sequences in the nuclear ribosomal DNA intergenic transcribed spacer (ITS) regions as those of P. lactiflora. 9,10) All of those samples were also confirmed to meet the criteria of paeoniflorin (not less than 2.0%) prescribed in the Japanese Pharmacopoeia 11) (data not shown). ICP-MS Analysis All samples (10-50 g) were dried and ground to powder.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations